(3fXe OYe GdbQGQGJ (B/s - (3GdSGdej, YdGA YHO GdQRGb eMeOs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2005)
(3eaGgje CSGSjI(B- (3GdEOGQI hUfY GdbQGQ(B- (3fXe GdeYdheGJ GdOGYeI dEJNGP GdbGQGQJ GdEOGQjI(B- (3fXe OYe GdbQGQGJ GdeJbOeI(B- (3CSS GdPcGA GdEUWfGYj(B- (3fXe OYe GdbQGQGJ hJWHjbGJ GdPcGA GdEUWfGYj(B( (3GdCfXeI GdNHjQI(B)- (3fXGe EcJSGH GdeYQaI(B- (3fXe OYe GdbQGQGJ hGdEOGQI GdEdcJQhfjIs
Keywords: (3EJNGP GdbQGQGJ(B- (3GdEOGQIs; (3GdbQGQGJ GdGOGQjIs